INTERNATIONAL HERITAGE CONSERVATION PRINCIPLES IN EARTHQUAKE ZONES, JAPAN - Masuda, Kanefusa; Mendoza Shimada, Olga Keiko (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The Lima Declaration, adopted at the “International Symposium on Disaster Risk Management of Cultural Heritage; Sustainable Conservation of Urban Cultural Heritage in Seismic Zones” on December 3, 2010, says at its beginning that “World is divided into seismic and non seismic areas. Earthquakes occur mainly along two big circles: The Circum-Paciic where more than 95% of seismic energy is dissipated and the Eurasian circle. Following the International Conservation Charters and conservation policies, now we address the cumulative damage to cultural heritage associated with severe earthquakes prone areas.” Japan and Peru are both located on the Circum-Paciic Seismic Zones, and also have rich cultural heritage, including many UNESCO World Heritage cultural sites. The structures of these heritage are mainly constructed with earthen, stone or wooden material, all ecological and natural materials, easy to reuse again for the reconstruction works after the earthquake disasters. For their sustainable protection and safety for human life, we need to constantly take care for the structures and be prepared for the next earthquake disasters based on management plans. Heritage values after reconstruction deeply depends on craftsmanship, one of the four tests of authenticity in the evaluation of World Heritage sites. Our heritage values are thus deeply related with intangible values, like techniques and community traditions. The Venice Charter in 1964 and the Nara Document on Authenticity in 1994, both guiding principles for the World Heritage system, and both adopted in seismic countries like Italy and Japan, do not have enough tools necessary for sustainable protection against earthquakes. We need careful understanding of existing conservation principles, but if they are not enough, we have to examine a new principle to solve this problem. This paper intends to clarify the above points, introducing recent disaster experiences in Japan, especially the case of East Japan Great Earthquake in 2011 and Kobe Earthquake in 1995.